DEVELOPMENT OF LEARNING MEDIA AND STUDENT WORK SHEETS ON FORCE AND WORK-ENERGY MATERIALS BASED LOCAL CULTURE TOOLS IN THE PHYSICS SCIENCE LEARNING FOR JUNIOR HIGH SCHOOL - Fakhruddin Z Fakhruddin Z; Yennita Yennita; Hendar Sudrajad (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2017)
The purpose of this study was to examine the validity of experimental tools and student worksheets resulting from research based on traditional cultural tools on the topic of force, newton’s law, work and energy. The research method used is research and development or Reseacrh and Development. This research was conducted in physics education laboratory of PMIPA FKIP University of Riau with the subject of experiment media research based on traditional culture equipment on the topic of force, newton’s law, work and energy with data source three physics education experts and two senior teachers as validator. The data analysis used is descriptive analysis that categorizes the average validity scores of experimental tools and student worksheets on force, newton’s laws, work and energy based of traditional cultural equipment. Based on data analysis, the research results obtained the average score with good category and very good, both for the validity of the experimental tool and for the student worksheet for all aspects. It shows experimental tools and student worksheets based on traditional cultural tools are valid and can be used as experimental tools and worksheets of junior physics students.